A novel synonymous variant in the NF1 gene disrupting splicing contributes to neurofibromatosis pathogenesis - Lin, Tao; Chen, Zheyan; Dong, Biwen; Pan, Haojie; Wang, Hai; Zheng, Xianjue; Chen, Kaixin; Lai, Yanan; Zhang, Chenhui; Dong, Ye; Xu, Zitong; Lin, Menmen; et al. (Frontiers in Genetics, 2025)
BackgroundNeurofibromatosis type 1 (NF1) is a common autosomal dominant genetic disorder characterized by café-au-lait macules, neurofibromas, and other manifestations. It is caused by variations in the NF1 gene located on chromosome 17q11.2. The gene’s complexity and extensive variations often lead to misdiagnoses by conventional detection methods, which adverses to effective diagnosis and treatment strategies.Case presentationA 26-year-old Chinese woman was admitted to our hospital with multiple café-au-lait spots and cutaneous nodules. She had a family history of NF1, with her mother also showing similar dermatological symptoms. Whole exome sequencing (WES) identified a synonymous variation, NM_001042492.3: c.987A>G (p.K329K), in the NF1 gene. Although synonymous variations are typically considered non-pathogenic, RNA sequencing (RNA-seq) and minigene analysis revealed that this variation caused the partial loss of exon 9, leading to aberrant splicing. These findings were validated through Sanger sequencing, confirming the genetic alteration and its impact on mRNA splicing.ConclusionThe case highlights the critical role of synonymous variations in the NF1 gene that significantly impact splicing and protein function. These findings expand our understanding of NF1’s genetic diversity and underscore the importance of comprehensive genetic and RNA analyses to achieve accurate diagnosis and in-depth insight into the molecular underpinnings of NF1.